Device-Related Complications Associated with Magec Rod Usage for Distraction-Based Correction of Scoliosis - Aakash Agarwal; Amey Kelkar; Ashish Garg Agarwal; Daksh Jayaswal; Arvind Jayaswal; Vithal Shendge (Spine Surgery and Related Research, 2020)
Introduction: Recent literature identifies similar failure rates such as anchor pull-out and rod breakage, but a higher unplanned revision surgery with MAGEC rods than with traditional growth rods. Besides known failure modes such as rod fracture, infection, etc., failure to noninvasively distract the rods was cited as the main cause of such unplanned surgeries. The source of these data ranges from multicenter cohort studies to singular case series. These studies included explanted implants that had undergone failure in distraction mechanism, rod fracture, or infection, or had reached their maximum length. Nevertheless, in addition to identifying the overall mode of failure, it is equally important to identify the large-scale incidence of exclusive failures in comparison with standard instrumentation failure modes in spine surgery. Methods: The US Food and Drug Administration (FDA) Manufacturer and User Facility Device Experience (MAUDE) databases were searched for reports on MAGEC rods, and on standard instrumentation used for spinal fusion. The adverse events were recorded, tabulated, and analyzed. Results: A search of the US FDA MAUDE database yielded reports of 163 device-related adverse events. These included distraction mechanism failure (n=129), rod fracture (n=24), and minor voluntary reports of infection and tissue discoloration (n=10). For standard instrumentation usage in spine surgery, pedicle screw breakage post surgery (n=336), set screw damage during surgery (n=257), rod breakage post surgery (n=175), interbody cage breakage during surgery (n=118), and pedicle screw breakage during surgery (n=75) were identified as the top 5 failure modes. Conclusions: The study identified the distraction mechanism failure as the most common and growing complication associated with MAGEC rod usage in children with scoliosis, leading to unplanned invasive revision surgeries.